Analysis of humus formation and factors for driving the humification process during composting of different agricultural wastes - Zhao, Bing; Wang, Yuyun; Sun, Huarong; Xu, Zhi (Frontiers in Environmental Science, 2022)
Composting can convert organic materials into stable humus (HS), resulting in high-fertility organic fertilizers, which were widely used in the treatment of agricultural wastes. Therefore, it would be beneficial to strengthen the degree of composting humification by exploring the formation law and main influencing factors of composting humification for different agricultural wastes. In this study, straw, cabbage, chicken manure, and pig manure were used as research objects, and the industrial mixed-material strip-stack composting and the single-material laboratory reactor composting were carried out, respectively. The results showed that the industrial mixed-material composting mode was beneficial to the continuation of the high temperature period for composting (The heat lasts for 20 days), and the high lignin treatment T2 (straw + chicken-manure composting) helped to promote the degradation of lignin and formation of humic acid (HA). At the end of composting, the absolute degradation of lignin in T2 treatment increased by 13.18% and 120.02% (P<0.01) compared with T1 (straw + cabbage + chicken-manure) and T3 (straw + pig-manure) treatments, respectively (P<0.01), and the humic acid (HA) content increased by 11.78% and 26.59% (P<0.05). In the single-material laboratory reactor composting system, the continuous high temperature period (31 days) contributed to the degradation of the composting materials and the formation of HA in straw (TS) composting treatment; at the end of composting, the absolute degradation amount of TS lignin increased by 137.98%, 170.99% and 196.82% compared with TV (cabbage), TC (chicken-manure) and TP (pig-manure) treatments (P<0.01), and the HA content increased by 281.76%, 377.57% and 460.71% (P<0.01). Redundancy analysis showed that temperature was the main environmental factor affecting the decomposition and humification process of composting organic materials; the increase of lignin absolute degradation was helpful to promote the formation of HA. This study found that temperature was the main environmental factor which drove lignin degradation and promoted the humification process of agricultural waste composting; the lignin content in the composting material was the basis for the formation of HA, and the absolute degradation amount of lignin was the main material factor that promoted the humification process.